Osteology of Batrachuperus londongensis (Urodela, Hynobiidae): study of bony anatomy of a facultatively neotenic salamander from Mount Emei, Sichuan Province, China - Jiang, Jian-ping; Jia, Jia; Zhang, Meihua; Gao, Ke-Qin (PeerJ, 2018)
The Longdong Stream Salamander Batrachuperus londongensis, living in a mountain stream environment at Mt. Emei in Sichuan Province, China, represents a rare species that is facultatively neotenic in the family Hynobiidae. Although the species has been known to science for some 40 years since its initial discovery in the late 1970s, anatomical details of its osteology remain poorly understood and developmental information is still lacking for the species. This study (1) provides a detailed osteological account of B. londongensis based on micro-CT scanning and clearing and staining of multiple specimens from the type locality; (2) provides a discussion of intraspecific variation related to life-history differences; and (3) presents a discussion on limb features related to morphological evolution of limb patterns correlative with ecological adaptation to mountain stream environments. Osteological comparisons with congeneric species has led to recognition of several diagnostic features that are unique to B. londongensis, including: vomers widely separated from one another, lacking a midline contact; presence of uncommon perichondral ossification of the ascending process of the palatoquadrate as part of the suspensorium; and presence of a prominent posterodorsal process of the scapular blade, which serves as a ligamentous insertion of the levator muscle of the scapula. In addition, some but not all neotenic individuals retain the palatine as a discrete element, indicative of its delayed absorption after sexual maturity. Postmetamorphic and neotenic individuals are strikingly different in the complexity of hyobranchial structures. Neotenes display a high degree of ossification of hyobranchial elements, tend to increase ossification of both hypobranchial I and ceratobranchial I during aging, and retain fully ossified ceratobranchial III and IV; in contrast, these elements remain entirely cartilaginous or are totally lost by resorption in postmetamorphic individuals. In addition, all postmetamorphic forms display an inverted “T”-shaped basibranchial II, whereas neotenes show transformation from a “fork”-shaped to the “T”-shaped configuration after sexual maturity. B. londongensis displays a mosaic of apomorphic and plesiomorphic states in its limb ossifications: presence of a single centrale element in both the manus and pes is a derived condition in Hynobiidae and other families as well, whereas retention of a postminimus in the pes is obviously plesiomorphic within Urodela. Reduction in number of digits from five to four in the pes and possession of a cornified sheath covering the terminal phalanges are also derived features shared with some but not all mountain stream salamanders that are adapted to a similar type of environment.
Keywords: Batrachuperus londongensis; Hynobiid salamander; Facultative neoteny; Osteology; Character evolution